2019
DOI: 10.1038/s41467-019-13772-4
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of the global carbonate weathering carbon-sink flux to climate and land-use changes

Abstract: The response of carbonate weathering carbon-sink flux (CCSF) to its environmental drivers is still not well understood on the global scale. This hinders understanding of the terrestrial carbon cycle. Here, we show that there is likely to be a widespread and consistent increase in the global CCSF (ranging from + 9.8% (RCP4.5) to + 17.1% (RCP8.5)) over the period 1950–2100. In the coming years the increasing temperature might be expected to have a negative impact on carbonate weathering. However, the increasing … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
54
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(71 citation statements)
references
References 46 publications
8
54
1
Order By: Relevance
“…The Shaliu River, with a length of 110 km and a catchment area of 1442 km 2 (Zhang et al, 2013) and a mean annual daily discharge of 7.5 m 3 s −1 from 2015 to 2016 (from Gangcha hydrological station), is the second largest river flowing into the Qinghai Lake on the northeastern edge of the Qinghai-Tibetan Plateau at an altitude of 3200-3800 m above sea level (Fig. 1a).…”
Section: Study Areamentioning
confidence: 99%
See 3 more Smart Citations
“…The Shaliu River, with a length of 110 km and a catchment area of 1442 km 2 (Zhang et al, 2013) and a mean annual daily discharge of 7.5 m 3 s −1 from 2015 to 2016 (from Gangcha hydrological station), is the second largest river flowing into the Qinghai Lake on the northeastern edge of the Qinghai-Tibetan Plateau at an altitude of 3200-3800 m above sea level (Fig. 1a).…”
Section: Study Areamentioning
confidence: 99%
“…The Shaliu River is a small river in-tegrating headwater streams of orders of 1-3 on the Qinghai-Tibetan Plateau. It flows through a semiarid alpine region widely covered by seasonally frozen soils (Wang et al, 2018) and is relatively well protected from human activities (Zhang et al, 2013;Cheng et al, 2018). The Shaliu River basin is covered by grassland (∼ 71 %) dominated by Potentilla anserina Rosaceae, Elymus nutans Griseb and Deyeuxia arundinacea (Liu et al, 2018); bare land (16 %); and wetland (10 %; Cheng et al, 2018).…”
Section: Study Areamentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies have been performed on the highly sensitive response of karstification to environmental change, such as to changing temperature and precipitation, the instability of DIC in karst water 8,9 and the complexity of DIC sources 10,11 . Sand-Jensen et al 12 observed that the ratio of HCO 3 -/CO 2 increased from 4 to 140 when the pH value of a freshwater lake ranged from 7.0 to 8.5, indicating that the characteristics of karst groundwater were partial alkaline with high concentrations of HCO 3 -.…”
Section: Introductionmentioning
confidence: 99%